Preoperative Functional Anxiety: A Conceptual Framework - McEachern, Marie (Operating Room Nurses Association of Canada Journal, 1992)
Preoperative functional anxiety is an important phenomenon for the patient undergoing surgical intervention. Functional anxiety facilitates the patient’s ability to cope with surgery. Personal control en- hances the patient’s coping and modifies anxiety to a functional level. The phenomenon of preoperative functional anxiety and related concepts of coping and locus of control have a direct effect on the concept of postoperative recovery. Current research is focusing primarily on preoperative anxiety' levels and postoperative recovery. There is a need for further nursing research to develop nursing theory about the concepts of coping and personal control as they relate to preoperative functional anxiety and postoperative recovery. This paper focuses on the development of a conceptual framework for understanding the, biopsychosocial phenomenon of preoperative functional anxiety.